The leisure experiences of university students with physical disabilities in Ireland. Issue 4 (1st October 2016) - Martin, Stephanie; Griffiths, Colin
ABSTRACT: Students with physical disabilities should have equal access to leisure activities as their peers without disabilities. The aim of this study was to explore the factors that influence the participation of university students with physical disabilities in leisure activities. This qualitative study, guided by the social model of disability, reported on findings from two focus groups: one with university staff members and one with students with physical disabilities. The results revealed that students with physical disabilities engaged in some leisure activities although they encountered environmental barriers that impeded participation. Staff members were conscious of the difficulties in creating a barrier-free environment for the participation of these students and were working on initiatives that would support the inclusion of students with disabilities in leisure activities on campus.